Crime and criminal behavior - Chambliss, William J. (Key issues in crime and punishment., 2011)
Crime and Criminal Behavior delves into such hotly debated topics as age of consent, euthanasia and assisted suicide, gambling, guns, internet pornography, marijuana and other drug laws, religious convictions, and terrorism and extremism. From using a faking I.D. to assaulting one's domestic partner to driving drunk, a vast array of behaviors fit into the definition of criminal. The authors of these 20 chapters examine the historical contexts of each topic and offer arguments both for and against the ways in which legislators and courts have defined and responded to criminal behaviors, address.